Preparation of Zn/Al-chitosan Composite for the Selective Adsorption of Methylene Blue Dye in Water - Mohadi, Risfidian; Siregar, Patimah Mega Syah Bahar Nur; Palapa, Neza Rahayu; Lesbani, Aldes (UI Scholars Hub, 2022)
Layered double hydroxide (LDHs) are widely used adsorbents for methylene blue removal. However, LDHs have a perishable structure that cannot be used repeatedly. Modifying LDHs with chitosan produces a strong material with a large surface area for methylene blue adsorption. Adsorption conditions were optimized by determining the adsorption isotherms and the adsorbent regeneration process. Results showed that the adsorption process was balanced in 90 min with maximum adsorption capacities of 86.207 mg/g, 35.336 mg/g, and 98.039 mg/g for Zn/Al, chitosan, and Zn/Al-chitosan, respectively. The adsorption in this study followed the Freundlich isotherm model. Regeneration analysis of the adsorbent showed that Zn/Al-chitosan can be used repeatedly in methylene blue adsorption.